Macrophytes, epipelic biofilm, and invertebrates as biotic indicators of physical habitat degradation of lowland streams (Argentina) - Cortelezzi, Agustina (2013)
Our objective was to assess the effect of the physical habitat degradation in three lowland streams of Argentina that are subject to different land uses. To address this matter, we looked into some physical habitat alterations, mainly the water quality and channel changes, the impact on macrophytes’ community, and the structural and functional descriptors of the epipelic biofilm and invertebrate assemblages. As a consequence of physical and chemical perturbations, we differentiated sampling sites with different degradation levels. The low degraded sites were affected mainly for the suburban land use, the moderately degraded sites for the rural land use, and the highly degraded sites for the urban land use. The data shows that the biotic descriptors that best reflected the environmental degradation were vegetation cover and macrophytes richness, the dominance of tolerant species (epipelic biofilm and invertebrates), algal biomass, O₂ consumption by the epipelic biofilm, and invertebrates’ richness and diversity. Furthermore, the results obtained highlight the importance of the macrophytes in the lowland streams, where there is a poor diversification of abiotic substrates and where the macrophytes not only provide shelter but also a food source for invertebrates and other trophic levels such as fish. We also noted that both in benthic communities, invertebrates and epipelic biofilm supplied different information: the habitat’s physical structure provided by the macrophytes influenced mainly the invertebrate descriptors; meanwhile, the water quality mainly influenced most of the epipelic biofilm descriptors.